Pastor, Politician, Entrepreneur, Chief: Power and Leadership on Epoon Atoll Today - Berta, Ola Gunhildrud (Anthropologica, 2020)
In analysing the various types of political figures and status positions on Epoon, an outer atoll in the Marshall Islands, this article sheds light on contemporary constitutions of hierarchy, authority and leadership. This leads to an argument about the context-dependent nature of power. No leadership figure on Epoon today is all-powerful in the sense that his or her influence is relevant across all political and cultural spheres. When the historical depictions of Marshallese chiefs are traced in a critical light, it will become clear that earlier ideas of the chiefs as autocratic power figures may have appeared to benefit German colonial administration and Protestant missionaries. Shifting the focus to the dynamics of contemporary leadership practices, the case of an El Salvadorian castaway illuminates the power plays various actors engage in to gain access to his boat. What we will see is that power is highly dependent on context to have effect.